Generation, characterization, and use of EKLF(Klf1)/CRE knock-in mice for cell-restricted analyses - Xue, Li; Mukherjee, Kaustav; Kelley, Kevin A.; Bieker, James J. (Frontiers in Hematology, 2024)
EKLF/Klf1 is a tissue-restricted transcription factor that plays a critical role in all aspects of erythropoiesis. Of particular note is its tissue-restricted pattern of expression, a property that could prove useful for expression control of a linked marker or enzymatic gene. With this in mind, we fused the CRE recombinase to the genomic EKLF coding region and established mouse lines. We find by FACS analyses that CRE expression driven by the EKLF transcription unit recapitulates erythroidrestricted expression with high penetrance in developing embryos. We then used this line to test its properties in the adult, where we found EKLF/CRE is an active and is a robust mimic of normal EKLF expression in the adult bone marrow. EKLF/CRE is also expressed in erythroblastic island macrophage in the fetal liver, and we demonstrate for the first time that, as seen during embryonic development, EKLF is also expressed in adult BM-derived erythroblastic island macrophage. Our data also support lineage studies showing EKLF expression at early stages of hematopoiesis. The EKLF/CRE mouse lines are novel reagents whose availability will be of great utility for future experiments by investigators in the red cell field.-Mice with CRE expression under the control of the EKLF promoter have been established -These exhibit highly penetrant CRE activity that precisely mimics endogenous EKLF expression patterns in fetal liver and adult erythroid cells as well as in island macrophages -These mice have been used to demonstrate that adult bone marrow macrophages retain similar phenotypic properties as their fetal liver counterpart